2016
DOI: 10.1016/s2095-3119(16)61415-6
|View full text |Cite
|
Sign up to set email alerts
|

Pyramiding of Pi46 and Pita to improve blast resistance and to evaluate the resistance effect of the two R genes

Abstract: Utilization of R (resistance) genes to develop resistant cultivars is an effective strategy to combat against rice blast disease. In this study, R genes Pi46 and Pita in a resistant accession H4 were introgressed into an elite restorer line Hang-Hui-179 (HH179) using the marker-assisted backcross breeding (MABB) procedure. As a result, three improved lines (e.g., R1791 carrying Pi46 alone, R1792 carrying Pita alone and R1793 carrying both Pi46 and Pita) were developed. The three improved lines had significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…In this study, two indica accessions, H4 and Huazhan, were used as donor parents (DPs). The accession H4, conferring broad-spectrum resistance to blast at both seedling and adult stages, was found to carry at least two major R genes, with Pi46 on the long arm of chromosome 11 (Xiao et al 2011) and Pita on chromosome 12 (Xiao et al 2016). The R gene Pi46 was confirmed to be a different allele of Pik / Pi1 locus, for several SNPs that could discriminate them were identified (data not shown).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, two indica accessions, H4 and Huazhan, were used as donor parents (DPs). The accession H4, conferring broad-spectrum resistance to blast at both seedling and adult stages, was found to carry at least two major R genes, with Pi46 on the long arm of chromosome 11 (Xiao et al 2011) and Pita on chromosome 12 (Xiao et al 2016). The R gene Pi46 was confirmed to be a different allele of Pik / Pi1 locus, for several SNPs that could discriminate them were identified (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, some broad-spectrum resistant varieties were identified to harbor multiple R genes, including Tetep (Barman et al 2004), IR64 (Sallaud et al 2003), Sanhuangzhan 2 (Liu et al 2004), Digu (Chen et al 2004; Shang et al 2009) and Gumei2 (Wu et al 2005). These findings suggest that the combination of multiple race-specific R genes is an effective strategy to develop cultivars with broad-spectrum resistance to blast disease (Hittalmani et al 2000, Tacconi et al 2010, Khanna et al 2015, Xiao et al 2016). However, multiple R genes mean intensive pressure to promote the evolution of M. oryzae races, which is highly various in population due to a high level of genomic instability of the pathogen (Dean et al 2005; Ballini et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, there were plants which had both the aroma and blast resistance genes, similar to the findings by Luo et al [24] who reported a successful development of WH6725 resistant line to blast disease which possessed both genes. In the present study, the presence of Pita gene in resistant or moderately resistant plants may be attributed to the fact that Pita gene has been found to confer a medium-spectrum resistance [25].…”
Section: Discussionmentioning
confidence: 99%
“…Pyramiding of multiple genes can lead to broad-spectrum disease resistance. For example, the Pi21 + Pi34 + qBR4-2 + qBR12-1 genes together [141], the Pi5 + Pi54 + Pid3 + Pigm genes together [140] and the Pik + Pita genes [142] were stacked to achieve broad-spectrum resistance to blast pathogen M. oryzae.…”
Section: Marker-assisted Gene Pyramiding For Blast Pathogens In Ricementioning
confidence: 99%